(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
In this study, the effects of geraniin on osteoprotegerin/receptor activator of nuclear factor-κB ligand(OPG/ RANKL) in regulating the proliferation of osteoblasts and suppression of osteoclast-like cells (OLC) in OLC-osteoblast co-cultured system in vitro were investigated. Osteoblasts were cultured and identified with alkaline phosphatase (ALP), gomori stain, and mineralized nodule stain. OLCs were isolated from long bones of Sprague–Dawley (SD) rats and identified with tartrate-resistant acid phosphatase(TRAP) stain. Methyl thiazolyl tetrazolium assay was used to examine the proliferation of osteoblasts, and immunocytochemistry and in situ hybridization to analyze the expression OPG/RANKL in osteoblasts co-cultured with osteoclasts under the action of geraniin, respectively. Geraniin could regulate the proliferation of osteoblasts MC3T3-E1, decrease the number of OLC in OLC-osteoblast co-cultured system, and inhibit the bone resorption areas and resorption pits of OLC in vitro experiments. Geraniin could promote the mRNA and protein expression levels of OPG and suppress those of RANKL in osteoblasts. These results indicate that geraniin has a promoting effect on the proliferation of osteoblasts and an inhibitory effect on the osteoclastic bone-resorption through regulating OPG/RANKL signaling pathway in OLC-OB co-cultured system.